(3GdHMK GdYdej hGSJNOGe eUGOQ GdeYdheGJ GdJbdjOjI hGdGdcJQhfjIs - (3YGeQ(B, (3bfOjdLjs ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2008)
(3JGQjN GdHMK GdYdej heSJdReGJg hCfhGYg, NWhGJ GYOGO GdHMK, efgL GdHMK GdYdej, GdYjfGJ hCOhGJ LeY GdeYdheGJ, cJGHI GdTcd GdfgGFj ddHMK, eUGOQ GdeYdheGJ GdJbdjOjI hGSJNOGeYG aj GdHMK, eUGOQ GdHMK GdGdcJQhfjI, THcI GfJQfjJ hGSJNOGeGJgG aj GdHMK GdYdej, GdehGbY GdHMKjI GdGdcJQhfjI Ydi GdGfJQfjJ, JhKjb GdeUGOQ hGdeYdheGJ hGSJNOGe GdecJHI aj GdHMKs
Keywords: (3GdGfJQfjJs; (3GdHMhKs; (3eUGOQ GdeYdheGJs